PERAN BRAND TRUST MEMEDIASI HUBUNGAN BRAND IMAGE DENGAN BRAND LOYALTY (Studi Pada Konsumen Iphone di Kota Denpasar) - Rodiques, Yolanda; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 7 No 3 (2018)DO - 10.24843/EJMUNUD.2018.v7.i03.p07, 2018)
This study aims to explain the role of brand trust in mediating the relationship of brand image with brand loyalty. The study was made in Denpasar city with the number of samples of 100 respondens iPhone smartphone users who have repurchases (at least 2 times of purchases) of the product. The sample is determined using non-probability sampling model, with purposive sampling technique. Data analysis technique used is path analysis and sobel test. The results showed that all hypotheses were accepted. Brand image has a positive and significant influence to brand trust, brand image has a positive and significant effect to brand loyalty, brand trust has a positive and significant influence to brand loyalty, brand trust has a positive and significant effect on mediating the relationship of brand image with brand loyalty. In the future, the company is expected to launch a maximum and innovative marketing campaign (advertisement) to raise the social class image of the iPhone users in the society and increase the level of consumer confidence in regard to the security aspect of the iPhone products.